Dampak Penggunaan Bahan Bakar Pertalite Terhadap Unjuk Kerja Daya, Torsi Dan Konsumsi Bahan Bakar Di Sepeda Motor Bertransmisi Otomatis - Jaya Saputra, Trisma; Fauzi, Luqman; Nur Amirul Huda, Dimas; Putra Arianto, Zegananda; Atsafiqi , Munadi (Rifa'Institute, 2023)
This study aims to investigate the effect of using Pertalite fuel on the performance of power, torque and fuel consumption on motorcycles with automatic transmission. The experimental method used by collecting data shows the performance of motorcycles using Pertalite fuel and comparing them to motorcycles using lower octane fuel. Various parameters such as maximum power, maximum torque and fuel consumption were measured and compared between the two groups. The results showed that the use of Pertalite fuel had a positive effect on power performance on automatic transmission motorcycles. The maximum power produced by an engine using Pertalite is higher than that of an engine using low octane fuel. In addition, the use of Pertalite also contributes to an increase in engine torque at certain engine speeds. However, in terms of fuel consumption, although the use of Pertalite has the potential to improve fuel efficiency, the results of this study show significant variations depending on the operating conditions and settings of the motorcycle. This study provides insight into the effect of using Pertalite fuel on the performance of power, torque, and fuel consumption on motorcycles with automatic transmission. The implications of this research can be used by motorcycle manufacturers and consumers in considering the use of fuel according to their needs and preferences.